Novel transcriptomic mechanisms of brain aging - Cavalier, Alyssa Nicole, author; LaRocca, Thomas, advisor; Lark, Daniel, committee member; Hamilton, Karyn, committee member; Weir, Tiffany, committee member (Colorado State University. Libraries, 2023)
As the world ages, the incidence of age-related diseases like dementia is expected to increase. Brain aging is characterized by declines in cognitive function that may develop into mild cognitive impairment, which increases the risk for dementia. In fact, age is the primary risk factor for late-onset Alzheimer's disease, which is the most common age-related dementia. The adverse cellular and molecular processes that underlie cognitive decline with aging in the brain are known collectively as the "hallmarks of brain aging." Advances in next-generation sequencing (e.g., transcriptomics/RNA-seq) have made it possible to investigate age- and disease-related changes in the brain at the broad gene expression level, and to identify potential therapeutic targets. With the support of my committee and mentoring team, I completed three studies using transcriptomics that characterize novel mechanisms that underlie brain aging. My findings include: (1) doxorubicin chemotherapy accelerates brain aging at the gene expression level, (2) apigenin nutraceutical supplementation targets age-related inflammation in the brain and rescues cognitive impairment in old mice, and (3) epigenetic dysregulation of transposable elements (remnants of viral infection in the genome) with aging contributes to age-related inflammation in Alzheimer's disease. Together, my work provides insight into transcripts and cellular/molecular pathways that are modifiable and may be therapeutic targets to delay or prevent consequences of brain aging.
Keywords: Alzheimer's disease; RNA-seq; aging; transcriptomics; brain aging